2002
DOI: 10.1002/jmri.10197
|View full text |Cite
|
Sign up to set email alerts
|

MR assessment of left ventricular function: Quantitative comparison of fast imaging employing steady‐state acquisition (FIESTA) with fast gradient echo cine technique

Abstract: Purpose:To evaluate the agreement of fast imaging employing steady-state acquisition (FIESTA) cine technique with segmented k-space fast gradient echo (GRE) cine technique when using them for assessment of cardiac function. Materials and Methods:Eleven MR cine studies were performed on six healthy volunteers and five patients, using FIESTA and fast GRE techniques. The quantitative measurements of ventricular function obtained from the two techniques were compared. The data analysis was performed by two observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
36
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 17 publications
8
36
0
Order By: Relevance
“…These variables also showed the smallest variation for interobserver variability. The results of intraand interobserver variability analysis in this study are comparable to the results of other studies with SSFP for all variables (6,(25)(26)(27)(28). Therefore, CMR imaging is an accurate and reliable method for follow-up of these variables and can adequately assess changes in ventricular size and global ventricular performance.…”
Section: Discussionsupporting
confidence: 84%
“…These variables also showed the smallest variation for interobserver variability. The results of intraand interobserver variability analysis in this study are comparable to the results of other studies with SSFP for all variables (6,(25)(26)(27)(28). Therefore, CMR imaging is an accurate and reliable method for follow-up of these variables and can adequately assess changes in ventricular size and global ventricular performance.…”
Section: Discussionsupporting
confidence: 84%
“…Their accuracy in determining left ventricular (LV) mass was also evaluated in animal experiments (10). Normal values were established for left and right ventricular volumes and function for both TGE as well as SSFP sequences, with SSFP sequences yielding significantly larger end-diastolic and end-systolic volumes (EDV and ESV, respectively) than TGE sequences (7,8,(11)(12)(13)(14)(15)(16)(17).Signal intensity in images acquired with SSFP sequences relies on T2/T1 ratio and does not depend on inflowing fresh blood, facilitating the delineation of papillary muscles and trabeculae as well as atrioventricular and semilunar valves (8). Contrast between intraventricular blood and myocardium as well as between myocardium and epicardial fat is significantly higher in images obtained with SSFP sequences compared to those acquired with TGE sequences (8,9), and thus…”
mentioning
confidence: 99%
“…Planning variability is due to the positional variation and angular deviation of the imaging planes from the optimum, and is prominent only in automated CMR planning. Intraobserver variability (11)(12)(13)16,36,37) arises due to subjectivity in myocardial border tracing by the human observer. The decomposition of the total variation showed that the relative contribution of the interstudy variability factors was significantly larger than that of the intraobserver factor for all CMR measurements (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the intraobserver variability accounted for the smallest part (15-29%) of the total variation and remained independent from the errors in placing the SA imaging planes. This contradiction can be partially explained by the fact that the BFFE sequence provides high-quality images with excellent contrast between blood and cardiac muscle (11,15,16,39). Thus, the slightly oblique orientation of the imaging planes with respect to the myocardial wall that arises in automated CMR planning does not affect the quantification of the LV dimensions and function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation